Activities of Transnational Organized Criminal Groups Detrimental to Critical Infrastructure Objects: Providing Qualification to Reduce Negative Impact on Sustainable Societal Development - Khoronovskyi, Oleg; Drozd, Oleksii; Minchenko, Serhii; But, Yurii; Bulatin, Dmytro (European Journal of Sustainable Development, 2025)
The purpose of the Article is to conduct legal assessment of the activities of transnational organized criminal groups detrimental to critical infrastructure objects from the perspective of criminal law and administrative law qualification to reduce their negative impact on sustainable societal development. Methodology. The following methods are used in the research: logical, dialectical, monographic, dogmatic, normative analyses, system and structural, statistical method, legal modelling. Findings. It is noted that a mandatory stage of the criminal law qualification of such activities is the determination of a foreign element. The correct establishment of all subjective and objective signs of such criminal offenses is one of the main prerequisites for developing theoretical provisions of the methodology for their investigation. Regarding administrative law qualification, it is noted that it is an element of the law enforcement activities of state authorities. It includes the choice of legal norm applicable in a specific case. In this event, the ascertainment of a number of circumstances is mandatory. Practical Implications. It is summarized that a properly conducted legal assessment of the transnational organized criminal groups’ activities detrimental to CIOs allows to achieve substantial results in their prevention and investigation, as well as reduce negative impact on socio-economic progress of the society. Keywords: critical infrastructure objects, criminal law qualification, administrative law qualification, evaluation, legal assessment, transnational organized crime, societal development